Back injuries in the young athlete - D'Hemecourt, P. A.; Gerbino, P. G.; Micheli, L. J. (Clinics in Sports Medicine, 2000)
The diagnosis of back pain in the young athlete should be specific and not attributed to nonspecific, mechanical causes. Risk factor identification and intervention are required. Treatment is then initiated in a specific pattern, addressing flexibility and muscular imbalances. Bracing is often used to allow healing of growth tissue. The lumbosacral orthosis may be molded in a lordotic posture to unload the disc or antilordotic posture to relieve the posterior column; however, customizing the lordosis to the individual biomechanics may be required. Spinal stabilization is initiated with therapy for strengthening isolated weaknesses and progressing to coactivation and proprioceptive techniques, such as the balance ball. Returning to competition is preceded with sport-specific training.